#### Answer

M = ((a+c),(b+d))

#### Work Step by Step

(2a,2b) and (2c,2d)
Using theorem 10.1.2 Midpoint formula
M = ($x_{m}, y_{m}) $ = ($\frac{x1+x2}{2}$, $\frac{y1+y2}{2}$)
M = ($\frac{2a+2c}{2}$, $\frac{2b+2d}{2}$) = ((a+c),(b+d))

Published by
Brooks Cole

ISBN 10:

ISBN 13:

M = ((a+c),(b+d))

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.